Ethics in Higher Education and Problem-Based Learning (Asian Education Studies, 2018)
Based on the daily problematics of the current globalized world, this article aims to reiterate the relevance of Ethics’ studies in higher education. The analysis utilises the Problem-Based Learning (PBL) concept and the Kantian reflections on education to offer a constructive way to stimulate students’ moral growth. The study begins with an introduction of its significance, then it considers the materials studied and the methodology used. Through the collection of bibliographical data, a descriptive approach to Howard Barrows‘ instruction method and the Kantian thought is given. Afterwards, the paper explains the harmonization between both, showing how Ethics can and should be debated during professional training. It also explains the role of the PBL in this process, concluding that both are the perfect combination for allowing not only the students but also the tutors, to develop their individual common sense and to better adapt to unexpected challenges.